2006
DOI: 10.1200/jco.2005.04.4339
|View full text |Cite
|
Sign up to set email alerts
|

Association of the PDCD5 Locus With Lung Cancer Risk and Prognosis in Smokers

Abstract: A B S T R A C T PurposeWhole-genome scan association analysis was carried out to identify genetic variants predictive of lung cancer risk in smokers and to confirm the identified variants in an independent sample. Patients and MethodsA case-control study was performed using two pools consisting of DNA from 321 German smoking lung cancer patients and 273 healthy smoking controls, respectively. A replication study was carried out using 254 Italian lung adenocarcinoma (ADCA) patients and 235 healthy controls. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 22 publications
3
72
0
Order By: Relevance
“…PDCD5 is downregulated in the lung adenocarcinoma patients compared to the healthy controls, which indicates PDCD5 is a tumor suppressor gene associated with lung cancer (34). Single nucleotide polymorphism in the PDCD5 gene locus was also found to be associated with non-small cell lung cancers (35).…”
Section: Introductionmentioning
confidence: 90%
“…PDCD5 is downregulated in the lung adenocarcinoma patients compared to the healthy controls, which indicates PDCD5 is a tumor suppressor gene associated with lung cancer (34). Single nucleotide polymorphism in the PDCD5 gene locus was also found to be associated with non-small cell lung cancers (35).…”
Section: Introductionmentioning
confidence: 90%
“…12,13 Pooled DNA samples have been analysed for several generations of DNA-based genetic markers such as microsatellite and candidate SNPs using several technologies, including using the Affymetrix GeneChip Mapping 100K Array. [14][15][16][17][18][19][20] To date, however, the empirical validity of DNA pooling and genotyping using array technology has not been sufficiently demonstrated to enable researchers to apply the method with confidence in WGA experiments.…”
Section: Introductionmentioning
confidence: 99%
“…As an apoptosis related gene, PDCD5 has been proved to be involved in malignancy pathogenesis by increasing evidences. Downregulation of PDCD5 expression has been found in various malignancies, such as breast cancer [8] , hepatocellular carcinoma [9] , cervical cancer [10] , gastric cancer [11] , lung cancer [12] , acute and chronic myelogenous leukemia [13][14][15] , astrocytic gliomas [16] , prostate cancer [17] and papillary thyroid carcinoma (PTC) [3] . Inhibition of PDCD5 expression by siRNA could inhibit cell apoptosis [19] , and the sensitivity of HeLa cells to apoptosis induced by etoposide is reduced by in situ electroporation of the anti-PDCD5 monoclonal antibody [20] .…”
Section: Discussionmentioning
confidence: 99%
“…by accelerating apoptosis and cooperating with radiotherapy and chemotherapy [3][4][5][6][7] . Also, the decreased expression of PDCD5 has been reported in various human tumors, such as breast cancer [8] , hepatocellular carcinoma [9] , cervical cancer [10] , gastric cancer [11] , lung cancer [12] , acute and chronic myelogenous leukemia [13][14][15] , astrocytic gliomas [16] and prostate cancer [17] . Recently, an ELISA method for detecting soluble PDCD5 protein was established by scientists in Peking University Center for Human Disease Genomics and it was found that soluble PDCD5 could be detected in normal human peripheral blood (personal communication).…”
Section: Introductionmentioning
confidence: 99%